Analysis of the USDA’s 2017 Cow-Calf Management Practices Results: Part 2—Breeding Practices/Reproductive Technologies - Mario Binelli; João Bittar; Angela Gonella (EDIS, 2021)
This paper discusses the use of breeding practices and reproductive technologies in cow-calf operations, and the ways they affect calf crop. Written by Mario Binelli, João Bittar, and Angela Gonella, and published by the UF/IFAS Department of Animal Sciences, December 2021.